Detoxification mechanisms of black soldier fly larvae against microcystin-LR - Wenna Bao; Xinying Li; Haifeng Pan; Yingzi Gao; Linan Zhao; Jingsong Liu; Siyi Wang; Yinyi Zhang (Functional & Integrative Genomics, 2026)

Spatiotemporal variations and factors associated with surface urban heat islands in South Asia - Linan Sun; Longjue He; Haojie Liu; Peng Kang; Lan Wang; Jvjie Jia; Yuanzheng Li (Urban Climate, 2026)

Effect of microplastics on arsenic transport in shallow groundwater of coastal transition zones - Yizi Hua; Yuan Xue; Zhi Li; Yuting Zhang; Qinglong Liu; Linan Liu; Jingchun Tang (Water Research, 2026)

Perfluorooctanoic acid (PFOA) disrupts marine carbon sequestration potential of diatom Phaeodactylum tricornutum by regulating carbon-silicon coupling - Zhi Li; Yizi Hua; Yuan Xue; Linan Liu; Yuting Zhang; Lan Wang; Gang Wang; Qiang Li; Jingchun Tang (Journal of Hazardous Materials, 2026)

Cytological and molecular genetic evidence of feminized male gametophyte in the brown alga Saccharina japonica - Xiufeng Zhou; Cailing Yi; Nianchao Xue; Yan Li; Juan Sun; Shuxiu Chen; Yuting Zhai; Liang Shi; Yanling Liu; Nan Zhao; Xia Li; Xiaojie Li; et al. (Algal Research, 2026)

Construction of icariin-loaded bone powder/PLA composite scaffold and its effect on osteogenic differentiation of hADSCs - Weiting Guo; Xinyue Liu; Yingchao Liu; Jingjing Zhu; Langyu He; Yiran Tang; Yuen Yee Cheng; Xiangqin Li; Linan Li; Hongfei Wang; Kedong Song (Tissue and Cell, 2026)

All in one: AIE-featured carbon dots with antibacterial activity for multivariate detection of Ag+, Hg2+ and BSA in real samples - Yu Gao; Linan Zhou; Qingqing Peng; Tingting Cui; Ziyi Guan; Fang Zhang; Li Wang; Huiyi Yang; Fang Chai (Journal of Environmental Chemical Engineering, 2026)

Genomic insights into adaptation and microevolution of two novel non-AOA Nitrososphaeria, Acidarchaeum fankouense and Thermosulfuris yongpingense, in acid mine drainage ecosystems - Licao Chang; Xikai Su; Wenzhe Hu; Yun Fang; Jun Liu; Jintian Li; Linan Huang; Wensheng Shu (Systematic and Applied Microbiology, 2026)

Inequality in distribution of atmospheric particulate matters and their health exposure risk in Beijing-Tianjin-Hebei, China - Linan Guo; Yuehan Wang; Yi Yang; Yurong Zheng; Li Zhou; Wenbin Sun (Atmospheric Pollution Research, 2026)

A single PCR-based sex marker, Sj-SexI, from conserved SDR gametologue genes: Enhancing efficiency and cross-species applicability in kelp - Liping Liu; Zihan Gai; Yan Li; Yanling Liu; Shuxiu Chen; Xiaojie Li; Weiwei Wang; Linan Zhang (Aquaculture, 2026)

Synergistic utilization of desulfurization gypsum and flue gas for the sustainable synthesis of nano-CaCO3 - Lufei Wang; Linan Su; Mingxu Li; Can Lv; Weizhong Zhao (Chemical Engineering Journal, 2026)

Protective role of nano-selenium on Gymnocypris przewalskii under saline–alkaline stress: a comprehensive analysis of transcriptomics and metabolomics - Yanxia Chen; Zhaonan Li; Ying Yang; Tianxiu Liang; Shuchen Huang; Jingjing Zhang; Wenjie Jin; Linan Wang; Qingchun Yan; Changzhong Li (Fish Physiology and Biochemistry, 2026)

AUV path planning method for data collection in underwater wireless sensor network - Zongyu He; Qian Sun; Yibing Li; Linan Ma; Yujie Huang (Ocean Engineering, 2026)

Humic acid modulates Fe(II) mediated chromium reduction in simulated marine-terrestrial interlaced zones: A double-edged sword effect - Yuan Xue; Yizi Hua; Zhi Li; Yuting Zhang; Linan Liu; Jingchun Tang (Journal of Hazardous Materials, 2026)

Coagulation enhancing the formation of aerobic granules in low-strength wastewater - Cheng Zeng; Linan Yu; Haoran Xu; Yuanyuan Cheng; Long Cheng; Lingcong Zeng; Shaoqin Li; Bei Long (Journal of Water Process Engineering, 2025)

Homologous nanocellulose modification: A “like cures like” strategy against coffee-ring and infiltration effects in paper-based colorimetric detection - Linan Sun; Yafei Lou; Siyu Chen; Hongyue Weng; Jiahao Li; Zhihui Lin; Junfei Tian; Rong Cao (Analytica Chimica Acta, 2025)

Viral insights into the acidification of sulfidic mine tailings - Xikai Su; Jun Liu; Licao Chang; Wenzhe Hu; Yun Fang; Jintian Li; Linan Huang; Wensheng Shu; Hailiang Dong (Journal of Hazardous Materials, 2025)

Iron-silicon modified biochar for remediation of cadmium/arsenic co-contaminated paddy fields: Is it possible to kill two birds with one stone? - Han Wu; Linan Liu; Jingmin Sun; Xin He; Zichuan Li; Jingchun Tang (Journal of Hazardous Materials, 2025)

Combined semi-continuous feeding and stripping: Improving volatile fatty acid production and sulfate reduction in a two-phase anaerobic sulfate reduction system - Sifang Wang; Zerong Jiang; Linan Zhao; Kaoming Zhang; Ziyao Chen; Shilin Li; Yu Miao; Chun Hu; Zhu Wang (Environmental Research, 2025)

Polyploid breeding of Saccharina japonica: Harnessing aposporous reproduction - Pingping Tian; Yan Li; Nianchao Xue; Weiwei Wang; Shuxiu Chen; Yanling Liu; Juan Sun; Guangjin Liang; Juping Zhao; Liang Shi; Nan Zhao; Xia Li; et al. (Aquaculture, 2025)

Stacking paper sheets into multi-purpose quick response sensing code with built-in nitrocellulose-membrane-free lateral flow assay for detecting tetracycline in food samples - Rong Cao; Yafei Lou; Zhiyuan Yang; Linan Sun; Azadeh Nilghaz; Miaosi Li; Junfei Tian (Food Chemistry, 2025)

Apomixis in kelp genetic improvement: Practices, challenges, and prospects - Linan Zhang; Nianchao Xue; Xiaojie Li; Xiufeng Zhou; Guanpin Yang (Aquaculture, 2025)

Preparation and antibacterial activity of p-coumaric acid-β-cyclodextrin complex against Alicyclobacillus acidoterrestris in apple juice - Xuemei Meng; Tong Zhang; Jun Li; Xiya Cao; Linan Duan; Haitian Fang; Junnan Xu (Innovative Food Science & Emerging Technologies, 2025)

Achieving efficient water-electricity ensemble via using easily obtainable hydrovoltaic-thermoelectric hybrid generators - Jiacheng Hu; Jiangchao Huang; Yaxian Chen; Linan Xu; Bingquan Wu; Haotian Yue; Houqiang Ji; Haitao Li; Jian Jin (Desalination, 2025)

Correlation of cyclosporine A blood concentration with kidney injury for pediatric patients after hematopoietic stem cell transplantation: a retrospective cohort study - Wei Shi; Xin Qiu; Liang Huang; Linan Zeng; Runxin Lu; Hailong Li; Kun Zou; Zhijun Jia; Guo Cheng; Qin Yu; Limei Zhao; Lingli Zhang (European Journal of Clinical Pharmacology, 2025)

Integrated response surface and machine learning approach: Experimental optimization and DFT analysis for NaN3 removal via NaClO oxidation - Yunfeng Tan; Jiangzhou Qin; Shengquan Chang; Shengqiang Ma; Linan Su; Nengsheng Liu; Quanlin Zhao; Xintao Wang; Chenxi Li; Jinmao Ma; Kun Wu; Zhengfang Ye (Journal of Water Process Engineering, 2025)

The quantity, reliability, transparency, reporting, and interpretation of pharmacovigilance signal detection studies in pregnancy: a meta-epidemiological study - Xue-Feng Jiao; Zhengyang Zhang; Lixiong Gong; Shan Lan; Songzhen Zhang; Jiang Wang; Xiubi Chen; Qiang Wei; Hailong Li; Linan Zeng; Lu Han; Lingli Zhang (European Journal of Clinical Pharmacology, 2025)

Controllable construction of ratiometric fluorescent probe based on Ag/Au nanoclusters and silicon nanoparticles for multivariate detection of Ag+, Cu2+, and Hg2+ - Jingyu Pang; Linan Zhou; Zhuang Liang; Tingting Li; Rui Yan; Fang Chai (Journal of Environmental Chemical Engineering, 2024)

Reference guides for the safe use of drugs during pregnancy: a systematic review and comparative analysis - Xue-Feng Jiao; Panda Qiu; Zheyun Song; Xue Peng; Hailong Li; Linan Zeng; Lingli Zhang (European Journal of Clinical Pharmacology, 2024)

Climate‐related naturally occurring epimutation and their roles in plant adaptation in A. thaliana - Bowei Chen; Min Wang; Yile Guo; Zihui Zhang; Wei Zhou; Lesheng Cao; Tianxu Zhang; Shahid Ali; Linan Xie; Yuhua Li; Gaurav Zinta; Shanwen Sun; et al. (Molecular Ecology, 2024)
DNA methylation has been proposed to be an important mechanism that allows plants to respond to their environments sometimes entirely uncoupled from genetic variation. To understand the genetic basis, biological functions and climatic relationships of DNA methylation at a population scale in Arabidopsis thaliana , we performed a genome‐wide association analysis with high‐quality single nucleotide polymorphisms (SNPs), and found that ~56% on average, especially in the CHH sequence context (71%), of the differentially methylated regions (DMRs) are not tagged by SNPs. Among them, a total of 3235 DMRs are significantly associated with gene expressions and potentially heritable. 655 of the 3235 DMRs are associated with climatic variables, and we experimentally verified one of them, HEI10 (HUMAN ENHANCER OF CELL INVASION NO.10). Such epigenetic loci could be subjected to natural selection thereby affecting plant adaptation, and would be expected to be an indicator of accessions at risk. We therefore incorporated these climate‐related DMRs into a gradient forest model, and found that the natural A. thaliana accessions in Southern Europe that may be most at risk under future climate change. Our findings highlight the importance of integrating DNA methylation that is independent of genetic variations, and climatic data to predict plants' vulnerability to future climate change.

Apomixis in Saccharina japonica: Parthenogenesis in male and apogamy in female gametophytes - Shutao Yue; Nianchao Xue; Cailing Yi; Juan Sun; Xia Li; Shuxiu Chen; Linan Zhang; Xiaojie Li (Aquaculture, 2024)

Responses of tropical forest soil organic matter pools to shifts in precipitation patterns - Feng Sun; Linan Fan; Guangyan Deng; Yakov Kuzyakov; Yue Zhang; Jinchuang Wang; Yingwen Li; Faming Wang; Zhian Li; Akash Tariq; Jordi Sardans; Josep Penuelas; et al. (Soil Biology and Biochemistry, 2024)

Heparin mimicking sulfonated polyester synergistically promotes bacterial Infected-Wound healing with ROS responsive cinnamaldehyde based prodrugs - Haiwei Liu; Pengfei Shan; Yingwen Lu; Xiaoyue Lian; Feng He; Jinxiang Xiao; Linan Qiu; Zhenghao Liu; Zuobin Gan; Qingshan Yan; Yupeng Qiu; Wenwen Lin; et al. (Chemical Engineering Journal, 2024)

Use of statins and risks of ovarian, uterine, and cervical diseases: a cohort study in the UK Biobank - Xue-Feng Jiao; Hailong Li; Linan Zeng; Huazhen Yang; Yao Hu; Yuanyuan Qu; Wenwen Chen; Yajing Sun; Wei Zhang; Xiaoxi Zeng; Lingli Zhang (European Journal of Clinical Pharmacology, 2024)
Purpose To examine the associations between use of statins and risks of various ovarian, uterine, and cervical diseases, including ovarian cancer, endometrial cancer, cervical cancer, ovarian cyst, polycystic ovarian syndrome, endometriosis, endometrial hyperplasia, endometrial polyp, and cervical polyp. Methods We conducted a cohort study among female participants in the UK Biobank. Information on the use of statins was collected through verbal interview. Outcome information was obtained by linking to national cancer registry data and hospital inpatient data. We used Cox proportional hazards regression to examine the associations. Results A total of 180,855 female participants (18,403 statin users and 162,452 non-users) were included. Use of statins was significantly associated with increased risks of cervical cancer (adjusted hazard ratio (HR), 1.55; 95% confidence interval (95% CI), 1.05–2.30) and polycystic ovarian syndrome (adjusted HR, 4.39; 95% CI, 1.68–11.49). However, we observed no significant association between use of statins and risk of ovarian cancer, endometrial cancer, ovarian cyst, endometriosis, endometrial hyperplasia, endometrial polyp, or cervical polyp. Conclusion Our findings suggest that use of statins is associated with increased risks of cervical cancer and polycystic ovarian syndrome, but is not associated with increased or decreased risk of ovarian cancer, endometrial cancer, ovarian cyst, endometriosis, endometrial polyp, or cervical polyp.

Revealing new insights: Two-center evidence of microplastics in human vitreous humor and their implications for ocular health - Yizhou Zhong; Yuhang Yang; Linan Zhang; Dahui Ma; Kailiang Wen; Jiachun Cai; Zhanmou Cai; Cui Wang; Xiaoyan Chai; Jingwen Zhong; Boxuan Liang; Yuji Huang; et al. (Science of The Total Environment, 2024)

Evidence that co-existing cadmium and microplastics have an antagonistic effect on greenhouse gas emissions from paddy field soils - Linan Liu; Xinzuo Yang; Rob M. Ellam; Qiang Li; Di Feng; Zhaoliang Song; Jingchun Tang (Journal of Hazardous Materials, 2024)

The in-situ generation of ClO• by single- and dual-atom catalysis of chloride ions to degrade sulfonamide antibiotics: A DFT study - Linan Shen; Xinyi Yu; Mingxue Li; Siqi Deng; Haijie Cao (Chemical Engineering Journal, 2024)

The tunable synthesis of orange emissive carbon dots for sensitive and selective detection of Hg2+ via portable paper sensor - Yu Gao; Linan Zhou; Zechang Li; Peng Sun; Qijun Dai; Ruifeng Xie; Fang Chai (Journal of Environmental Chemical Engineering, 2024)

CNT-based water-induced generator for effective self-powered devices via superior synergism between electrokinetic and galvanic effects - Linan Xu; Wenxing Wang; Xiaoguang Li; Hongjian Yu; Xinyuan Liu; Yang Zhang; Hongyang Xu; Song Lin; Xing Yi Ling; Haitao Li (Chemical Engineering Journal, 2023)

Incidence and risk factors of drug-induced kidney injury in children: a systematic review and meta-analysis - Miao Zhang; Bingchen Lang; Hailong Li; Liang Huang; Linan Zeng; Zhi-Jun Jia; Guo Cheng; Yu Zhu; Lingli Zhang (European Journal of Clinical Pharmacology, 2023)

A numerical study on desalination performance enhancement by bipolar ionic diode nanochannels - Tong Li; Ran Peng; Tingting Zhang; Chenjie Wang; Linan Guo; Yongxin Song; Junsheng Wang; Minyi Xu (Desalination, 2023)

An Underwater Triboelectric Biomechanical Energy Harvester to Power the Electronic Tag of Marine Life - Bo Liu; Taili Du; Xiaoyan Xu; Jianhua Liu; Peng Zhu; Linan Guo; Yuanzheng Li; Tianrun Wang; Yongjiu Zou; Hao Wang; Peng Xu; Peiting Sun; et al. (Journal of Marine Science and Engineering, 2023)
Implantable electronic tags are crucial for the conservation of marine biodiversity. However, the power supply associated with these tags remains a significant challenge. In this study, an underwater flexible triboelectric nanogenerator (UF-TENG) was proposed to harvest the biomechanical energy from the movements of marine life, ensuring a consistent power source for the implantable devices. The UF-TENG, which is watertight by the protection of a hydrophobic poly(tetrafluoroethylene) film, consists of high stretchable carbon black-silicone as electrode and silicone as a dielectric material. This innovative design enhances the UF-TENG’s adaptability and biocompatibility with marine organisms. The UF-TENG’s performance was rigorously assessed under various conditions. Experimental data highlight a peak output of 14 V, 0.43 μA and 38 nC, with a peak power of 2.9 μW from only one unit. Notably, its performance exhibited minimal degradation even after three weeks, showing its excellent robustness. Furthermore, the UF-TENG is promising in the self-powered sensing of the environmental parameter and the marine life movement. Finally, a continuous power supply of an underwater temperature is achieved by paralleling UF-TENGs. These findings indicate the broad potential of UF-TENG technology in powering implantable electronic tags.

Impact of different zero valent iron-based particles on anaerobic microbial dechlorination of 2,4-dichlorophenol: Comparison of dechlorination performance and the underlying mechanism - Cholnam Ri; Fengxiang Li; Hyokchol Mun; Linan Liu; Jingchun Tang (Journal of Hazardous Materials, 2023)

Flexible core–shell structured Al-Cu alloy phase change materials for heat management - Chixi Zhou; Lei Jiang; Zhenhua Gu; Chunliang Wang; Lun He; Linan Huang; Zhiqiang Li; Kongzhai Li (Chemical Engineering Journal, 2023)

New insight into the mechanisms of preferential encapsulation of metal(loid)s by wheat phytoliths under silicon nanoparticle amendment - Linan Liu; Zhaoliang Song; Jingchun Tang; Qiang Li; Binoy Sarkar; Robert Mark Ellam; Yangyang Wang; Xiangyu Zhu; Nanthi Bolan; Hailong Wang (Science of The Total Environment, 2023)

Three-dimensional quantitative structural-activity relationship and molecular dynamics study of multivariate substituted 4-oxyquinazoline HDAC6 inhibitors - Linan Zhao; Le Fu; Guangping Li; Yongxin Yu; Juan Wang; Haoran Liang; Mao Shu; Zhihua Lin; Yuanqiang Wang (Molecular Diversity, 2023)

Identification and Characterization of Long Non-Coding RNAs Involved in Sex-Related Gene Regulation in Kelp Saccharina japonica - Meihan Bai; Shutao Yue; Weiwei Wang; Xinxin Du; Xiaojie Li; Guanpin Yang; Linan Zhang (Journal of Ocean University of China, 2023)

Coupling and environmental implications of in situ formed biogenic Fe–Mn minerals induced by indigenous bacteria and oxygen perturbations for As(III) immobilization in groundwater - Xinxin Zhao; Zuoming Xie; Taikun Liu; Ping Li; Fuwen Pei; Linan Wang (Science of The Total Environment, 2023)

Silicon (Si) modification of biochars from different Si-bearing precursors improves cadmium remediation - Linan Liu; Xinzuo Yang; Shakeel Ahmad; Xiaolong Li; Cholnam Ri; Jingchun Tang; Robert Mark Ellam; Zhaoliang Song (Chemical Engineering Journal, 2023)

Design of hybrid La1-Ce CoO3- catalysts for lean methane combustion via creating active Co and Ce species - Lei Jiang; Danyang Li; Guixian Deng; Chunqiang Lu; Linan Huang; Zhiqiang Li; Haiwen Xu; Xing Zhu; Hua Wang; Kongzhai Li (Chemical Engineering Journal, 2023)

Ball-milled Fe0/FeS2 enhanced interaction of Shewanella oneidensis MR-1 with anaerobic microbial community: Impact on 2,4-dichloronitrobenzene reduction and methane yield - Cholnam Ri; Fengxiang Li; Hyokchol Mun; Linan Liu; Jingchun Tang (Chemical Engineering Journal, 2023)

Spatiotemporal variations, influence factors, and simulation of global cooling degree days - Yuanzheng Li; Tian He; Yuchan Wang; Linan Sun; Yi Yan; Guosong Zhao (Environmental Science and Pollution Research, 2022)

Study of the synthesis, adsorption property, and photocatalytic activity of TiO2/coal gasification fine slag mesoporous silica glass microsphere composite - Dandan Zhu; Linan Shi; Haoming Li; Jinyi Zhang; Jiupeng Zhang; Cundi Wei (Environmental Science and Pollution Research, 2022)

Safety of azithromycin in pediatrics: a systematic review and meta-analysis - Linan Zeng; Peipei Xu; Imti Choonara; Zhenyan Bo; Xiangchen Pan; Wenyan Li; Xiaofeng Ni; Tao Xiong; Can Chen; Leshan Huang; Shamim Ahmad Qazi; Dezhi Mu; et al. (European Journal of Clinical Pharmacology, 2020)
Purpose To evaluate the toxicity of azithromycin in neonates, infants, and children. Methods A systematic review was performed for relevant studies using Medline (Ovid), PubMed, Cochrane Central Register of Controlled Trials, EMBASE, CINAHL, and International Pharmaceutical Abstracts. We calculated the pooled incidence of adverse drug reactions (ADRs) associated with azithromycin based on prospective studies (RCTs and prospective cohort studies) and analyzed the risk difference (RD) of ADRs between azithromycin and placebo or other antibiotics using meta-analysis of RCTs. Results We included 133 studies with 4243 ADRs reported in 197,675 neonates, infants, and children who received azithromycin. The safety of azithromycin as MDA in pediatrics was poorly monitored. The main ADRs were diarrhea and vomiting. In prospective non-MDA studies, the most common toxicity was gastrointestinal ADRs (938/1967; 47.7%). The most serious toxicities were cardiac (prolonged QT or irregular heart beat) and idiopathic hypertrophic pyloric stenosis (IHPS). Compared with placebo, azithromycin did not show increased risk ADRs based on RCTs (risk difference − 0.17 to 0.07). The incidence of QT prolonged was higher in the medium-dosage group (10–30 mg/kg/day) than that of low-dosage group (≤ 10 mg/kg/day) (82.0% vs 1.2%). Conclusion The safety of azithromycin as MDA needs further evaluation. The most common ADRs are diarrhea and vomiting. The risk of the most serious uncommon ADRs (cardiac-prolonged QT and IHPS) is unknown.

Characteristics of indoor and outdoor fine particles in heating period at urban, suburban, and rural sites in Harbin, China - Wenxu Fang; Weiwei Song; Liyan Liu; Guangnian Chen; Linan Ma; Yuxuan Liang; Yujie Xu; Xueying Wang; Yehao Ji; Yu Zhuang; Amadou Hima Boubacar; Yifan Li (Environmental Science and Pollution Research, 2020)

Effects of Fungal Polysaccharide on Oxidative Damage and TLR4 Pathway to the Central Immune Organs in Cadmium Intoxication in Chickens - Ruyue Li; Linan Zhang; Zequn Tang; Tianqi Li; Guangxing Li; Ruili Zhang; Ming Ge (Biological Trace Element Research, 2019)

An integrated approach for landslide susceptibility mapping by considering spatial correlation and fractal distribution of clustered landslide data - Linan Liu; Shouding Li; Xiao Li; Yue Jiang; Wenhui Wei; Zhanhe Wang; Yaheng Bai (Landslides, 2019)

A genome screen for the development of sex-specific DNA markers in Saccharina japonica - Linan Zhang; Cuiju Cui; Yan Li; Hao Wu; Xiaojie Li (Journal of Applied Phycology, 2018)

Ecological stoichiometry of nitrogen, phosphorous, and sulfur in China’s forests - Yuntao Wu; Hongyan Liu; Zhaoliang Song; Xiaomin Yang; Zichuan Li; Qian Hao; Linan Liu (Acta Geochimica, 2017)

Impact of climate and lithology on soil phytolith-occluded carbon accumulation in eastern China - Xiaodong Zhang; Zhaoliang Song; Zhiqi Zhao; Lukas Van Zwieten; Jianwu Li; Linan Liu; Song Xu; Hailong Wang (Journal of Soils and Sediments, 2017)

Development of genic SSR markers from an assembled Saccharina japonica genome - Jie Peng; Linan Zhang; Xiaojie Li; Cuiju Cui; Ruina Wu; Pingping Tian; Yan Li; Yanling Liu (Journal of Applied Phycology, 2016)

Characterization of genome-wide microsatellites of Saccharina japonica based on a preliminary assembly of Illumina sequencing reads - Linan Zhang; Jie Peng; Xiaojie Li; Cuiju Cui; Juan Sun; Guanpin Yang (Journal of Ocean University of China, 2016)

Breeding of an intraspecific kelp hybrid Dongfang no. 6 (Saccharina japonica, Phaeophyceae, Laminariales) for suitable processing products and evaluation of its culture performance - Xiaojie Li; Zhuangzhi Zhang; Shancun Qu; Guangjin Liang; Nan Zhao; Juan Sun; Shaofeng Song; Zengmei Cao; Xia Li; Jinhua Pan; Shiju Luo; Linan Zhang; et al. (Journal of Applied Phycology, 2016)

Relationship between the velvet-like texture of flower petals and light reflection from epidermal cell surfaces - Yang Zhang; Tianxun Sun; Linan Xie; Takahiro Hayashi; Saneyuki Kawabata; Yuhua Li (Journal of Plant Research, 2015)

Development of 27 trinucleotide microsatellite markers for Saccharina japonica using next generation sequencing technology - Linan Zhang; Jie Peng; Xiaojie Li; Yanling Liu; Cuiju Cui; Hao Wu; Ruina Wu; Pingping Tian; Yan Li (Conservation Genetics Resources, 2014)

YAP-mediated regulation of the chondrogenic phenotype in response to matrix elasticity - Weiliang Zhong; Ying Li; Linan Li; Weiguo Zhang; Shouyu Wang; Xifu Zheng (Journal of Molecular Histology, 2013)

Effect of temperature on the development of Saccharina japonica gametophytes - Linan Zhang; Cuiju Cui; Xiaojie Li; Zhuangzhi Zhang; Shiju Luo; Guangjin Liang; Yanling Liu; Guanpin Yang (Journal of Applied Phycology, 2013)

Biodegradation of avermectin by Bacteroidetes endosymbiont strain LYH - Zaixing Li; Cunyi Song; Jingliang Yang; Jianbo Guo; Linan Xing (World Journal of Microbiology and Biotechnology, 2008)

Suppression of colorectal tumor growth by regulated survivin targeting - Binghua Li; Junkai Fan; Xinran Liu; Rong Qi; Linan Bo; Jinfa Gu; Cheng Qian; Xinyuan Liu (Journal of Molecular Medicine, 2006)